Comparative Analysis of Motor Vehicle Accident Compensation Systems in The United States and Canada: Legal Structures, Outcomes, and Policy Implications (2023) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Motor vehicle accident (MVA) compensation systems in North America adopts distinct policy approaches, with the United States emphasizing tort-based, fault-driven frameworks, and Canada employing primarily no-fault or hybrid models. This review draws evidence from academic literature, government reports, and insurance industry sources to compare system structures, benefits, and practical outcomes as of 2023. Major differences between these provinces include the speed of access to medical care, availability of income replacement, legal costs, and eligibility for non-economic damages such as pain and suffering. Generally, no-fault and hybrid systems provide faster, more predictable support, whereas tort-based systems allow higher potential awards but often involve delayed compensation and high legal fees. However, the differences that exists across states and provinces demonstrates jurisdiction-specific effects on recovery, equity, and financial burden. The review identifies knowledge gaps, including comparative recovery trajectories and long-term outcomes, and offers recommendations for policymakers, researchers, and clinicians to enhance evidence-based informed decisions. These findings support efforts to design compensation models that balance timeliness, fairness, and sustainability for individuals affected by motor vehicle accidents.